(untitled) (Conference Zone, 2022)
The world we live in is changing and developing beyond recognition. It is required to work according to the daily requirements in every field. In addition, many demands and responsibilities are placed on teachers working with the growing generation. A teacher needs to understand what modern students live with and be in tune with them. In this article, creativity is the main factor in the development of pedagogical activity.